BIMBINGAN TEKNIS PENOMORAN SURAT DAN KEARSIPAN UNTUK SELURUH UNIT DI LINGKUNGAN SEKOLAH TINGGI ILMU EKONOMI LMII - Desyana Putri; Karina Silaen (LPPM Universitas Ibnu Sina, 2022)
Every institution, agency, or enterprise, such as universities, engages in correspondence or correspondence as a routine activity. As one of Medan's private colleges, LMII College of Economics requires a clear policy for processing incoming and outgoing letters, including letter numbering and archives, as a form of administrative control. The goal of this community service project is to help this educational institution with letter numbering and excellent archiving practices in order to improve service quality for both internal and external parties through an organized mail and archive management program. The participatory service method was chosen as the service method. This activity took place on Thursday, January 13, 2022, with a total of ten participants, one from each unit within the LMII School of Economics. The preparation step is followed by the implementation stage, which involves material presentation, discussion, and direction, and finally the closing stage. The outcomes of the technical guidance's execution proceeded easily, and the participants gave it a favourable response.